Comparison of the risk of falls between elderly people who practice physical exercises and who are sedentary and the relationship between balance and muscle strength variables - Patrícia Martins Franciulli; Patrícia Anduz Souza; Paula Nunes Cordeiro Soares; Vitória Nascimento Silva; Yasmin Thainá Novais Severino; Yaizi Gabrielle dos Santos; Angélica Castilho Alonso (O Mundo da Saúde, 2019)
Falling is an event with an unfavorable outcome, which limits the independence and autonomy of the elderly, in addition to generating high social and economic costs. The risk of falls, in general, is assessed by individuals' physical abilities such as postural balance, mainly the dynamic type, and muscular strength. The primary objective of this study was to evaluate the effect of physical activity on the number and risk of falls, through postural balance, mobility and muscular strength of the elderly. Secondarily, this study aimed to correlate muscle strength with the variables of balance and mobility. A total of 76 elderly people participated in the study and were divided into group A, with 39 active elderly people (72.1 ± 2.2 years) who performed some type of physical activity at least twice a week, and group S, with 37 sedentary elderly people (71.8 ± 3.4 years) who did not engage in any type of physical activity. The number of falls was evaluated by a questionnaire and balance was evaluated by the Berg balance scale. For measuring mobility, the Timed up and go test was used, and for the handgrip strength a hand dynamometer was used. Student's t-test was performed to identify differences between groups, and Pearson's correlation was used for both groups between handgrip strength, balance and mobility. Group A demonstrated a lower number of falls (p=0.01*) and risk of falls according to the Berg scale (p=0.01*) and the TUG test (p=0.01*) compared with the S group. There was no difference (p=0.90) between handgrip strength and the other groups. There was no relationship between strength and balance variables. Physical activity has a positive effect on the risk of falls, but postural balance and muscle strength should be tested, associated and trained in a complementary way throughout life, because the biological aging process of the neuromuscular system has a deleterious effect between the components of balance and muscular strength.